2019
DOI: 10.2147/ndt.s219288
|View full text |Cite
|
Sign up to set email alerts
|

<p>Affective theory of mind in Parkinson’s disease: the effect of cognitive performance</p>

Abstract: Purpose Among other non-motor symptoms, theory of mind (ToM), the ability to recognize, understand and infer others’ mental states, beliefs, intents and wishes, has been shown to deteriorate during the course of Parkinson’s disease (PD). It has been speculated that ToM impairments could be related to cognitive deficits in PD. However, the current state of literature suggests that there is heterogeneity regarding the involvement of cognitive functioning in the relationship of PD and ToM. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 73 publications
2
22
0
1
Order By: Relevance
“…Insufficient cooperation leads to a further deterioration of the clinical condition of patients and consequently to the quality of life of both patients and their relatives. [41][42][43] The fact that a significant proportion of patients are in need of institutional care further increases health-care costs. 2 Timely device-aided therapeutical approaches can be a major breakthrough in the quality of life of many APD patients and may prolong the period during which the patient can be cared for within the confines of a family home.…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient cooperation leads to a further deterioration of the clinical condition of patients and consequently to the quality of life of both patients and their relatives. [41][42][43] The fact that a significant proportion of patients are in need of institutional care further increases health-care costs. 2 Timely device-aided therapeutical approaches can be a major breakthrough in the quality of life of many APD patients and may prolong the period during which the patient can be cared for within the confines of a family home.…”
Section: Discussionmentioning
confidence: 99%
“…Although not all studies have reported affective ToM deficiencies in advanced PD [ 38 ], Poletti et al [ 28 ] and Romosan et al [ 75 ] reported worsening affective ToM ability as the disease progresses. Although we did not find a significant correlation between ToM performance and disease duration, almost half of our sample consisted of patients in H&Y stages 3 and 4, which are considered moderate and advanced stages of PD; this could help to explain our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have linked performance of PD patients on affective ToM tasks with other cognitive deficiencies, including visuospatial ability, inhibition, cognitive flexibility, and working memory [ 23 , 27 , 75 ]. Although we found that differences in ToM performance between EOPD and controls were not mediated by overall cognitive ability, deficiencies in specific cognitive domains could have impacted performance in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…The negative correlations found between BPRS-E scores and MoCA scores (total, attention and memory) suggest that the presence of mild psychiatric symptoms coexists with cognitive impairments regarding attention and memory. The literature data show that while positive psychotic symptoms such as hallucinations and delusions have little or no association with cognitive dysfunctions, negative and disorganized symptoms show a stronger relationship with discrete cognitive impairments such as immediate recall, attention, verbal and non-verbal memory, verbal IQ and full-scale IQ [ 49 , 50 , 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%